2015
DOI: 10.1088/2041-8205/801/2/l31
|View full text |Cite
|
Sign up to set email alerts
|

A CHANDRASEKHAR MASS PROGENITOR FOR THE TYPE Ia SUPERNOVA REMNANT 3C 397 FROM THE ENHANCED ABUNDANCES OF NICKEL AND MANGANESE

Abstract: Despite decades of intense efforts, many fundamental aspects of Type Ia supernova (SNe Ia) remain elusive. One of the major open questions is whether the mass of the exploding white dwarf (WD) is close to the Chandrasekhar limit. Here we report the detection of strong K-shell emission from stable Fe-peak elements in the Suzaku X-ray spectrum of the Type Ia supernova remnant (SNR) 3C 397. The high Ni/Fe and Mn/Fe mass ratios (0.11-0.24 and 0.018-0.033, respectively) in the hot plasma component that dominates th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(198 citation statements)
references
References 50 publications
15
181
2
Order By: Relevance
“…The SD model is thought to have observable consequences and some classes of SD models have been observationally ruled out as the dominant channel (e.g., Leonard 2007;Bianco et al 2011;Chomiuk et al 2016;Maguire et al 2016), but there are a number of systems that are considered to be candidate progenitor systems (e.g. U Sco and V445 Pup; Li et al 2011) and there might be multiple channels for producing normal SNe Ia (e.g., Maguire et al 2013;Yamaguchi et al 2015). Current explosion simulations of both SD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The SD model is thought to have observable consequences and some classes of SD models have been observationally ruled out as the dominant channel (e.g., Leonard 2007;Bianco et al 2011;Chomiuk et al 2016;Maguire et al 2016), but there are a number of systems that are considered to be candidate progenitor systems (e.g. U Sco and V445 Pup; Li et al 2011) and there might be multiple channels for producing normal SNe Ia (e.g., Maguire et al 2013;Yamaguchi et al 2015). Current explosion simulations of both SD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For models with the same ρ c , increasing Z leads to a growth in both ratios; for models with the same Z, increasing ρ c shows similar results but at a steeper rate. We include the data from the remnant 3C 397 [20], which is known to have a high [Mn/Fe] ratio. In [20], one-dimensional SNIa models are explored to explain such feature.…”
Section: Resultsmentioning
confidence: 99%
“…We include the data from the remnant 3C 397 [20], which is known to have a high [Mn/Fe] ratio. In [20], one-dimensional SNIa models are explored to explain such feature. It is found that metallicity > 5Z ⊙ is required to explain such feature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the evolved Galactic SNR 3C 397, Yamaguchi et al (2015) found high ratios of Ni/Fe and Mn/Fe in the X-ray spectrum. As seen in Figure 2, the Ni/Fe and Mn/Fe ratios are among the highest reported for Type Ia SNRs, and strongly indicate that the progenitor must have exploded close to M Ch , which is more naturally explained by the SD scenario.…”
Section: Type Ia Snr -Progenitor Connectionsmentioning
confidence: 93%